Atividade antifúngica do óleo essencial de Cinnamomum zeylanicum Blume (canela) e sua associação com antifúngicos sintéticos sobre espécies de Candida - Castro, Ricardo Dias de (2010)
This study aimed to investigate the antifungal activity of essential oil (EO) of Cinnamomum zeylanicum Blume alone and combined with synthetic antifungal agents against Candida species. For this, it was determined the Minimum Inhibitory Concentration (MIC); Minimum Fungicidal Concentration (MFC); Fractional Inhibitory Concentration Index (FICI); microbial death curve promoted by the EO alone and combined with synthetic antifungals; action on fungal cell wall and interference of this combination on the fungal micromorphology. When assessed alone, C. zeylanicum and nystatin showed MIC of 312.5 μg/mL and 64 μg/mL, respectively. After combination, there was a reduction in MIC values for both substances, and were found values of respectively 39 μg/mL and 32 μg/mL for the EO and for Nystatin. It was verified a FICI value of 0.6024 (additivity). At all concentrations tested, these products alone and combined were able to reduce the number of CFU/mL, when compared with the control group from 30 min. It was also observed a reduction in the development of morphological structures of C. albicans cells, like pseudohyphae, blastoconidia and chlamydoconidia. When combined with miconazole, FICI values were 4.1248 (antagonism), 1.1248 (indifference) and 1.1248 (indifference), respectively, for C. albicans, C. tropicalis and C. krusei. Thus, it can be concluded that: C. zeylanicum showed activity against the Candida strains; this antifungal activity occurs, probably, by action of the essential oil in the process of fungal cell wall synthesis; the combination between C. zeylanicum EO and nystatin potentiated the inhibitory effect on growth of C. albicans strains, promoting a reduction in the development capacity of cellular morphologic structures. Nevertheless, the combination of C. zeylanicum EO and miconazole is not an advantageous possibility for growth inhibition of Candida spp.